War in Java: Historical Traces of Conflict and Struggle in the Indonesian Cultural Center - Rosyida, Esa Dina Inda; Prakoso, Lukman Yudho; Bermana, Seftiandra (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The land of Java has been a historical center of conflict and struggle that influenced the direction of Indonesian civilization. With a dense population and abundant cultural riches, the Land of Java witnessed various battles and political struggles that reflected the complex dynamics of its society. This article explores the historical traces of conflict and struggle in Java, starting from inter-kingdom battles in ancient history to the struggle against Dutch colonialists in the war of independence. Through analysis of Javanese cultural values, the role of important figures, and the impact of political and social transformation, this article illustrates how important the Land of Java is in shaping Indonesia's national identity. By understanding the history of conflict and struggle in Java, we can appreciate Indonesia's cultural heritage and gain deeper insight into the spirit of the nation's struggle.